DOING INTERFAITH DIALOGUE FOR PEACE - Canceran, Delfo (Asian Horizons, 2016)
This paper tackles the problematic relationship between religion and violence. Historically, religion is ambivalent in relation to peace and violence. Nonetheless, as peace advocates, we need to use the potential resources of religion as a way of advancing peace in a violent world. Interfaith dialogue is a tedious task not only because it needs time and patience in its engagements but also because of the complexities involved in this encounter. Thus, people engaged in interfaith dialogue must be open not only to sharing their experiences and views but also must be prepared to listen to questioning their positions and faiths. Since dialogue implies a whole worldview, not limited to religion, we need to learn from each other in the process of engagement in dialogue. We need to shift from a focus on our commonality to the recognition of our differences.